Neoliberalism and Applied Linguistics, by David Block, John Gray and Marnie Holborow. Routledge, 2012, 168 pp. - Hajar Abdul Rahim, (Kajian Malaysia, 2017)
Despite the wide spectrum of issues that have been addressed in applied linguistics, the authors of this book claim that the "economic and material bases of human activity and social life" have not received due attention from researchers (p. 4). In addressing this concern, the book set out to "reorient interdisciplinarianism in applied linguistics" by foregrounding the impact of political economy and neoliberal ideology on language, language teaching, teacher education and the conceptualisation of globalisation and identity in applied linguistics (p. 4). These are addressed in six elegantly presented chapters. Compact in size and number of pages, the book is quite unassuming except for its title Neoliberalism and Applied Linguistics which promises the challenging task of linking two fields whose connection is not immediately apparent.